Fe3o4 Templated Pyrolyzed Fe−N−C Catalysts. Understanding the Role of N-Functions and fe3c on the Orr Activity and Mechanism - Zagal-Moya, J; Zagal-Moya, J; Venegas-Toledo, R; Zuñiga-Loyola, C; Zuñiga-Loyola, C (John Wiley and Sons Inc, 2022)
Pyrolyzed non-precious metal catalysts have been proposed as an alternative to substitute the expensive and scarce noble metal catalysts in several conversion energy reactions. For the oxygen reduction reaction (ORR), the pyrolyzed catalyst M−N−C (M: Fe or Co) presents remarkable catalytic activity in acid and alkaline media. These pyrolyzed materials show a high heterogeneity of active sites being the most active in the MNx moieties. The activity and stability of these catalysts are also conditioned by other structural parameters such as the area, the N-doping, and by the presence of metal particles. In this study, we explore the use of Fe3O4 nanoparticles as templates and as iron sources to synthesize Fe−N−C. The best performance for the ORR in acidic media was reached with the catalysts using nanoparticles covered by PANI and iron salts as the precursor, with an onset potential of 0.85 vs. RHE and a direct 4-electrons mechanism. We corroborated the use of the catalysts’ redox potential as reactivity descriptors and discussed the detrimental role of the presence of Fe3C metallic particles in the mechanism. Based on the experimental results, we performed DFT calculations to explore the influence of N-doped species on the electronic density of the iron centers of FeN4 active sites, and we propose a theoretical model for increasing the activity based on the distance and ratio of N-doping to iron center. © 2022 The Authors. ChemElectroChem published by Wiley-VCH GmbH.